Pelayanan Farmasi dan Perbekalan Kesehatan pada Musim Haji Tahun 2012 di Sektor 3 Madinah, Arab Saudi - Winarsih, Winarsih; Mutiatikum, Daroham (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2013)
Service activities of Indonesian pilgrims in Madina, Saudi Arabia, which took place during the period September - November in 2012 consisted of two stages of the pre and the post Armina. In this study gives an overview of the implementation of services to the pharmaceutical and health supplies in sector 3 Madina. It also wants to know the availability of the drugs on sector 3 Madina and determine the amount of drug use ever. The design was a cross sectional study in which after processing the data it is known that there is a need for a drug that different during the two periods is both the number and types of medicines. But overall medicine and health supplies needs sector 3 Madinah can be met properly.